VEGETATIVE PROPAGATION OF FERNANSÁNCHEZ (Triplaris guayaquilensis) BY THE USE OF ROOTING HORMONES (ANA AND AIB) - Cruz Rosero, Nicolás (2008)
The present research was made out in Biotechnology Laboratory of Universidad Técnica Estatal ofQuevedo, the objective was to establish a vegetative propagation methodology for Triplaris guayaquilensis (Fernansánchez) with the rooting hormone use (ANA and AIB), as well as to determine the best treatment with the ANA and AIB hormone concentrations in the small branches rooting for this species. Complete Randomized Design with five experimental treatments in three repetitions and ten units by repetitions was used. At 45 days length by the greater root, number of roots, survival, and vigor was evaluated. The best treatments for Fernansánchez with (ANA and AIB) rooting was obtained with 1000 mg kg-1 ANA + 1000 mg kg-1 AIB concentrations for the length of greater root with 17.67 cm average, for the number of roots and survival, ideal concentration was 500 mg kg-1 ANA + 500 mg kg-1 AIB with five roots and 93.33% average and 1000 mg kg-1 ANA + 1000 mg kg-1 AIB concentration was ideal for vigor with 2.89, equivalent to 3 (high vigor). With this investigation it was demonstrated that the auxin ANA and AIB induce and improve the quality by roots on stakes, taking in consideration that these results cannot be generalized for other species.